Identifying people with multiple sclerosis in the Canadian Primary Care Sentinel Surveillance Network. Issue 4 (December 2019) - Marrie, Ruth Ann; Kosowan, Leanne; Taylor, Carole; Singer, Alexander
Background: We validated a case definition for multiple sclerosis using a clinical cohort linked with the Manitoba Primary Care Research Network of the Canadian Primary Care Sentinel Surveillance Network, and applied this definition to describe multiple sclerosis epidemiology using the Canadian Primary Care Sentinel Surveillance Network repository. Methods: We developed candidate case definitions for multiple sclerosis in the Manitoba Primary Care Research Network using diagnoses and medications. We compared these case definitions to multiple sclerosis diagnoses identified by applying a validated definition to population-based administrative data (reference standard 1) and multiple sclerosis diagnoses recorded by the provincial Multiple Sclerosis Clinic (reference standard 2) using sensitivity, specificity, positive predictive value and negative predictive value. We applied the preferred case definition to the national Canadian Primary Care Sentinel Surveillance Network dataset. Results: The Manitoba Primary Care Research Network included 160, 904 patients. The preferred case definition required ≥2 billing records for multiple sclerosis within 2 years or multiple sclerosis listed as a health condition or ≥1 multiple sclerosis-specific prescription. This definition had a low sensitivity versus administrative (44.25%) and clinic datasets (53.41%) but high specificity versus administrative data (99.95%). Specificity was lower versus clinic data (71.43%), but the positive predictive value was high. Conclusion: We developed a case definition for multiple sclerosis that can be applied to the Canadian Primary Care Sentinel Surveillance Network dataset for studies examining primary care of persons with multiple sclerosis.